Episiotomy and perineal repair workshop in Hospital Al-Sultan Abdullah - Abdullah, Bahiyah; Ahmad Sani, Nurul huda; Idris, Suriani; Asmary, Asmahani; Mohd Mohtar, Nur Faezza; Hashim, Erwina; Khairudin, Maziatun Nadia; Daud, Suzanna; Ravindran, Priyadharshini; Zakaria, Siti Nursofiani (Faculty of Medicine, 2026)
On 13 December 2025, the Episiotomy and Perineal Repair Workshop was successfully organised at Hospital Al- Sultan Abdullah (HASA), marking a milestone in advancing obstetric surgical education. This was the first hands-on surgical skills workshop by the Department of Obstetrics & Gynaecology (O&G), open to external participants. The workshop employed animal tissue models to facilitate realistic, ethical, and effective simulation-based learning, enabling participants to refine their technical skills in the assessment and repair of perineal trauma.